A new species of Diplasiolejeunea (Lejeuneaceae, Marchantiophyta) from Brazil - Prudêncio, Renato Xavier Araújo; Mello, Zélia Rodrigues De; Costa, Denise Pinheiro Da (Phytotaxa, 2018)
A bryological survey in southeastern Brazil revealed a new liverwort species, Diplasiolejeunea cubatensis from São Paulo State. The new species stands out having leaves without ocelli, cells with trigones and intermediate thickenings, flat lobules, very small underleaves which are as wide as stem, underleaf lobes only 2 cells wide at base and with the tip ending in a row of 2 cells, monoicous sexuality and perianths 5-keeled only in the upper half. The new species is described, illustrated and briefly discussed.